2021
DOI: 10.3390/molecules26154518
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Effects in the Antioxidant Activity of Extract from the Leaves of Cymbopogon citratus (DC) Stapf

Abstract: Cymbopogon citratus DC (Stapf.) is a perennial grass and it is distributed around the world. It is used as a condiment for food and beverage flavouring in the form of infusions and decoctions of its dried leaves. Our previous studies have shown antioxidant, anti-inflammatory and gastroprotective activities for the infusion and its phenolic fractions. The aim of the present work was to develop oral dosage forms from a Cymbopogon citratus extract to be used as a functional food with antioxidant properties. Initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
(52 reference statements)
0
2
0
1
Order By: Relevance
“…For example, Tazi et al (2024) demonstrated a significant qualitative and quantitative variation of bioactive molecules from the the extracts of C. citratus among samples growing in Asia, Europe, South America, and Africa. In parallel, current studies showed important quantities of total phenolic compounds and flavonoid contents and antioxidant activity [41,42], which are suggested to increase lemongrass biological activitiesʹ effectiveness.…”
Section: Introductionmentioning
confidence: 66%
“…For example, Tazi et al (2024) demonstrated a significant qualitative and quantitative variation of bioactive molecules from the the extracts of C. citratus among samples growing in Asia, Europe, South America, and Africa. In parallel, current studies showed important quantities of total phenolic compounds and flavonoid contents and antioxidant activity [41,42], which are suggested to increase lemongrass biological activitiesʹ effectiveness.…”
Section: Introductionmentioning
confidence: 66%
“…Langkah utama untuk memiliki kulit yang sehat yaitu dengan melakukan perawatan pada kulit, salah satunya dengan penggunaan lulur (Fauzi, 2012). Salah satu kerusakan yang diakibatkan oleh radikal bebas yaitu timbulnya masalah penuaan kulit (Azahar et al, 2017;Sousa et al, 2021). Radikal bebas dapat diredam dengan antioksidan, dimana antioksidan ini berperan dalam menstabilkan maupun menonaktifkan kerja dari radikal bebas yang akan menyerang sel dan berakibat menyebabkan kerusakan sel (Carmona-Hernandez et al, 2021;Sadowska-Bartosz & Bartosz, 2014).…”
Section: Pendahuluanunclassified
“…Polyphenol antioxidants have defensive effects against various infections, including cardiovascular and neurological diseases, as well as malignancies, and possess antioxidant components in rich sources responsible for medicinal properties [33][34][35]. Moreover, most of the polyphenols known so far, have been shown to be able to scavenge free radicals [36].…”
Section: Introductionmentioning
confidence: 99%